Hepatitis C viral infection among prisoners - Kostić Velimir (Vojnosanitetski Pregled, 2013)
Background/Aim. Hepatitis C virus (HCV) infection is an important sociomedical problem worldwide because the chronification of the disease is frequent and the occurance of liver cirrhosis and hepatocellular carcinoma can be expected. The aim of this study was to determine the way of infection, pathohistological changes of the liver, virus genotype presence and sustained virological response after pegylated interferon and ribavirin therapy in prison inmates. Methods. The study included 52 patients with chronic HCV infection classified in two groups managed during 2008-2010. The first group consisted of prisoners (n = 22) and the second one of “non-prisoners” (n = 30). The patients from both groups underwent diagnostic preparation (biochemical analyses, liver biopsy, hepatitis virus detection and genotypisation using polymerase chain reaction issue). The treatment lasted for 24 weeks for virus genotypes 2 and 3, and 48 weeks for genotypes 1 and 4. Results. All the patients were males, approximately the same age (35 ± 4.1 and 31 ± 7.6 years). Virus genotype 1 was significantly more frequent in the prisoners (p < 0.05), that demanded longer treatment (48 weeks). At the same time, statistically significant higher number of patients, “non-prisoners”, achieved a sustained virological response (p < 0.01). Conclusion. Intravenous drug abuse and tattoos, separately or together, are the most frequent way of infection in prisoners. Dominant presence of virus genotype 1 resulted in lower number of patients with sustained virological response, probably regardless prison environment and regime.